X-Ray CT Investigation on Fractal Characteristics of Fine-Grained Tailing Sand in Fujian’s Makeng: Insight into the Mesoscopic Seepage Failure - Dayu Long; Changhong Li; Yu Wang; Yueqi Shi (Geofluids)
This work is aimed at revealing the mesophysical process and mechanical behaviors of fine-grained tailing sand during seepage failure. The macroscopic seepage tests combined with posttest X-ray computed tomography (CT) were employed to study the fractal characteristics of mesostructure. Results show that before and after the seepage failure of fine-grained tailing sand, fractal of pore distribution (Dpd) and fractal dimension of pore size (Dps) show a relatively obvious positive correlation with porosity. Tailing particles migrate along the seepage direction during the seepage process, resulting in the gradual decrease of Dpd and pore distribution area. The Dps reflects the variation characteristics of pore number distribution with different pore sizes. The increase in Dps leads to a decrease in the uniformity of pore size and an increase in the size difference between pores. The mass fractal dimension (Dm) of fine-grained tailing sand samples ranges from 1.6472 to 1.8256. With the increase of Dm, the coefficient of uniformity (Cu) of tailing sand tends to increase. The Dm method can discern the seepage failure type of fine-grained tailing sand, and it is more accurate than the traditional method. This study provides a reference for the prevention and control of the seepage failure of tailing dam.